From Ideal to Real: Attachment Orientations Guide Preference for an Autonomous Leadership Style - Gruda, Dritjon; Kafetsios, Konstantinos (Frontiers in Psychology, 2022)
Autonomy is a key characteristic of attachment relations that varies as a function of attachment orientations and is also a key personality characteristic of leadership perceptions. In the presented research, we reasoned that the relationship between attachment and preference for specific leaders and leadership behavior would be a function of individuals’ insecure attachment strategies. We test our hypotheses in two studies. Study 1 uses Multiple Indicators Multiple Causes (MIMIC) modeling to test expectations based on a cross-sectional design, while Study 2 features a vignette-based experimental design. We find that anxious individuals attributed less positive evaluations to an autonomous leadership style (Study 1), while avoidant persons attributed higher leader competence to an autonomous leader description (Study 2). Compared to less anxious participants, highly anxious participants attributed lower competence to the autonomous leader description. By examining how individual differences in attachment orientations can indirectly influence the ideal leader categorization process, the present set of studies supports the importance of attachment orientations and related working models in leader perception and contributes to the literature on leader-follower fit. Using a survey and experimental approach, we examine how followers’ attachment schemas can shape the leader influence process, specifically concerning a preference for an autonomous leadership style.